And then came Brexit: Experiences and future plans of young EU migrants in the London region - Lulle, Aija; Moroşanu, Laura; King, Russell (Population space and place, 2018)
This paper investigates the potential rupture that the United Kingdom's “Brexit” referendum of June 23, 2016, might bring about in intra‐European Union youth mobilities, with a specific focus on the London region. In many respects, and counter‐intuitively given the Brexit result, London has already become a “Eurocity”: a magnet for young people, both highly educated and less educated, from all over Europe who, especially since the turn of the millennium, have flocked to the city and its wider region to work, study, and play. Now, these erstwhile open‐ended migration trajectories have been potentially disrupted by a referendum result that few anticipated, and whose consequential results are still unclear. The main theoretical props for our analysis are the notions of “liquid migration,” “tactics of belonging,” “whiteness,” “privilege,” and “affect.” Data are drawn from 60 in‐depth interviews with Irish, Italian, and Romanian young‐adult students and higher and lower skilled workers, carried out in late 2015 and early 2016, plus 27 reinterviews carried out in late 2016, post‐Brexit. Results indicate participants' profound and generally negative reaction to Brexit and, as a consequence, a diversity of uncertainties and of plans over their future mobility: either to stay put using “tactics of belonging,” or to return home earlier than planned, or to move on to another country. Finally, we find evidence that new hierarchies and boundaries are drawn between intra‐European Union migrants as a result of Brexit.